The impact of spot‐size on single‐photon avalanche diode timing‐jitter and quantum key distribution - Alexandra Lee; Alfonso Tello Castillo; Craig Whitehill; Ross Donaldson (IET Quantum Communication)
Abstract In free‐space implementations of Quantum key distribution (QKD), the wide adoption of near‐Infrared wavelengths has led to the common use of silicon single‐photon avalanche diodes (Si‐SPAD) for receiver systems. While the impacts of some SPAD properties on QKD have been explored extensively, the relationship of spot‐size and spatial position on the full instrumental response and thus quantum bit error rate (QBER) has been studied little. Changes in spot size and spatial position can result from atmospheric turbulence and pointing and tracking errors. Here, An empirical analysis of that relationship is presented utilising a large active area, 500 μm, free‐space coupled Si‐SPAD designed for free‐space QKD. A baseline full‐width at half‐maximum timing jitter of 182 ps and a QBER contribution of 0.1 % for a 1 GHz clock frequency QKD system and 100 ps time‐gating window are reported. The impacts of spot‐size and spatial position can increase the QBER to over 0.3%. The link between the spot‐size and timing jitter will allow the understanding of tolerancing for the alignment of Si‐SPADs within free‐space QKD receiver systems—an important factor in designing properly engineered practical systems and the equipment needed to compensate for atmospheric turbulence and pointing and tracking.